Waterborne Toxoplasmosis, Brazil, from Field to Gene - de Moura, Lenildo (Centers for Disease Control and Prevention, 2006)
Water was the suspected vehicle of Toxoplasma gondii dissemination in a toxoplasmosis outbreak in Brazil. A case-control study and geographic mapping of cases were performed. T. gondii was isolated directly from the implicated water and genotyped as SAG 2 type I.